2010
DOI: 10.1111/j.1365-2109.2010.02604.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of formalin and povidone-iodine disinfection techniques on the eggs of three marine finfish species

Abstract: Surface disinfection trials were performed on eggs from three marine finfish species: California yellowtail (CYT; Seriola lalandi), white seabass (WSB; Atractoscion nobilis) and California halibut (HA; Paralichthys californicus). All three species were spawned from captive populations maintained at the Hubbs‐SeaWorld Research Institute (HSWRI). Five disinfection treatments were used for each species; Treatment 1 included 100 mg L−1 of formalin (F100) for 60 min (current HSWRI treatment), Treatment 2 included 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 24 publications
2
50
0
3
Order By: Relevance
“…Therefore, egg disinfection against bacteria and fungi, is an important standard practice in artificial hatcheries. Egg disinfection prevents transfer of pathogens from broodstock to eggs [3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, egg disinfection against bacteria and fungi, is an important standard practice in artificial hatcheries. Egg disinfection prevents transfer of pathogens from broodstock to eggs [3].…”
Section: Introductionmentioning
confidence: 99%
“…6 CFU/g) were acceptable within the ranges of bacteria colonized on the surface of salmonid eggs (10 3 -10 6 CFU/g) (Austin 2006), however the viable counts in freshwater tilapia eggs taken in this study were higher than those in marine fish eggs. Treasurer et al (2005) reported the number of 3100 to 38 000 CFU/ml of egg in cod and haddock, while the colony counts in California yellowtail, white seabass, and California halibut were 16.7, 110.0, and 233.3 CFU/ml of egg, respectively (Stuart et al 2010). In our study, the bacterial counts (1.57 × 10 3 CFU/ml) in the hatchery water were comparable to those in the rearing system of California halibut (10 4 CFU/ml) (Stuart et al 2010) and of Mozambique tilapia (6.25 × 10 3 CFU/ml) (Subasinghe and Sommerville 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Treasurer et al (2005) reported the number of 3100 to 38 000 CFU/ml of egg in cod and haddock, while the colony counts in California yellowtail, white seabass, and California halibut were 16.7, 110.0, and 233.3 CFU/ml of egg, respectively (Stuart et al 2010). In our study, the bacterial counts (1.57 × 10 3 CFU/ml) in the hatchery water were comparable to those in the rearing system of California halibut (10 4 CFU/ml) (Stuart et al 2010) and of Mozambique tilapia (6.25 × 10 3 CFU/ml) (Subasinghe and Sommerville 1985). The relatively high numbers of bacteria colonized on the surface of Nile tilapia eggs may be attributed to the rapid growth of the waterborne pathogens in temperate water temperature, particularly in the hatchery facility that is in the tropical region as Thailand, and the gelatinous matrix surrounding the eggs may be an appropriate substrate for bacterial proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actualmente, existen diversos productos químicos para desinfectar los huevos de peces, entre los que se encuentran el iodo, la formalina, la acriflavina y el glutaraldehído que han sido utilizados en especies marinas con resultados efectivos (Van Waters 1988, Salvesen et al 1997, Tucker 1998, Escaffre et al 2001, Katharios et al 2007, Ibarra-Castro 2008. En peces marinos, el iodo se ha aplicado para desinfectar huevos de diversas especies, y se ha observado su eficiencia en cuanto a la reducción de la carga bacteriana (Katharios et al 2007, Stuart et al 2010. La acriflavina se ha usado tradicionalmente para desinfectar huevos de peces marinos como es el caso del barramundi (Lates calcarifer), obteniendo resultados de eclosión mayores de 80% (Tucker 1998, Álvarez-Lajonchère & Tsuzuki 2008.…”
Section: Introductionunclassified